RESOLUSI KONFLIK DI TAMAN NASIONAL TESSO NILO RIAU, INDONESIA: TINJAUAN RELASI PEMANGKU KEPENTINGAN - Handoyo Handoyo (Jurnal Analisis Kebijakan Kehutanan, 2015)
Conflict in Tesso Nilo National Park (TNNP) involves many actors that threaten its existence as an area aimed to conserving the ecosystem to the survival of the sumatran elephant. This study finds significance when it can identify the actors and provide one approach to managing stakeholder relationships through the power stakeholder analysis (PSA). The study results shows the actors involved in this conflict are: TNNP institution, local communities, migrant communities, investors of oil palm plantations, cooperatives, bad apparatures, local government, law enforcer and non-governmental organizations (NGOs). TNNP, local government and law enforcer are on the quadrant with the characteristics of stakeholders who have the power and high potential. Stakeholders in this quadrant can do a collaboration in order to strengthen the management. Investor of oil palm plantation, the national land agency (BPN) and NGOs are actors who have high power but low potential. Management of relationships that can be offered is that TNNP withstands the pressure from oil palm plantation investors to invest in the region of TNNP and take action to mitigate the impact of NGOs and BPN different perspective. Local communities and migrant communities have high potentials but have low power. TNNP can increase their capacity in national park management.